Using microscopic techniques for taxonomic implications of seed and fruits of Delphinium L. (sensu lato) (Ranunculaceae). Issue 2 (11th November 2019) - Hadidchi, Anahita; Attar, Farideh; Ullah, Fazal
Abstract: In present research, micromorphological characters of the genus Delphinium L. (sensu lato) Ranunculaceae seeds and fruits were studied using microscopic techniques. A total of 37 species were studied using light (LM) and scanning electron microscopy (SEM) to evaluate seeds and fruits micromorphological characteristics for the taxonomic identification and species relationship in the genus. For each taxon, 33 characters were observed and studied. All characters were analyzed using MVSP software and UPGMA method by using dissimilarity index (average taxonomic distance). Considerable differences were observed in trichomes shape of fruit and seed color features. The results revealed that all studied taxa are separated into three clades. The first clade consists of D. pallidiflorum and D. semibarbatum, which have black seed and two types of glandular and crispate trichomes in fruit. The second clade consists of D. speciosum, D. szowitsianum, D. dasystachyson, D. aquilegifolium, D. ursinum, C. trigonelloides, and C. camptocarpa, which had a brown color seeds, two types of glandular and villous trichomes on fruits also have been observed. The remaining species were classified as third clade having various colors including yellow, black, and brown color seeds, the trichome shapes included one of the following forms strigose, villous, trichomes less, glandular, hooked, and crispate trichomes in fruits. The aim of the present study is to use micromorphological characters of seeds and fruits for the taxonomic identification and species delimitation in the genus Delphinium . Abstract : Importance of seeds and fruits characteristics based on scanning electron microscopy (SEM) techniques. Systematic comparison and investigation to elucidate the taxonomic importance of seeds and fruits in the genus Delphinium L. (sensu lato). To find out potential characters for the phylogenetic relationships among the species of the genus Delphinium L. (sensu lato).